Use iteration, either forward or backward substitution, to solve the recurrence relation an=an−1−1 for any positive integer n, with initial condition, a0=1. Use mathematical induction to prove the solution you find is correct.
Arithmetic progression
"a_n=a+d(n-1)"
"a_n=a-n+1"
Let "P(n)" be the proposition that "a_n=a-n+1" for any positive integer "n."
Basis Step:
"P(1)" is true, because
"a_1=a-1+1=a"Inductive Step:
Assume that "P(k)" holds for an arbitrary positive integer "k." That is, we assume that
Under this assumption, it must be shown that "P(k + 1)" is true, namely, that
is also true.
Substitute
"a_{k+1}=a-(k+1)+1"
This last equation shows that "P(k + 1)" is true under the assumption that "P(k)" is true. This completes the inductive step
We have completed the basis step and the inductive step, so by mathematical induction we know that "P(n)" is true for all positive integers "n." That is, we have proven that
for all positive integers "n."
Comments
Leave a comment